Effectiveness of Counseling Using Motion Graphics Against Changes in Attitudes to Consuming Fast Food in Adolescents 2022 - Melly Kristanti; Nunuk Nugrohowati; Yanti Harjono; Vernanda Em Afdhal; Raden Roro Maya Dennisa; Nabila Fairuz (Faculty of Teacher Training and Education, Universitas Terbuka, 2023)
Media is very useful in increasing knowledge, especially in adolescents. Animated media is one of the ways in which education and information can be conveyed properly to adolescents. Therefore, the researchers wanted to see the effectiveness of motion graphics on the knowledge and attitudes of adolescents regarding fast food. This study used a cross sectional study design with a sample size of 120 samples. The instrument for this study used questionnaire pre-test and post-test. The analysis used in this study is the Wilcoxon test. There is a change in the attitude of adolescents after being given counseling using motion graphics, namely a p-value of 0.000 and knowledge did not experience a significant change p-value 0.165. Based on these results, it is certain that there is a need for changes in healthy living behavior to avoid obesity which has an impact on degenerative diseases. In addition, there is a need for new ways to provide counseling to adolescents, namely using motion graphics which are quite effective in providing information.